Simulation of Vetilligo Therapy Equipment - Hudha Wijaya, Nur; Agtesa, Adelia; De Brito Silva, Gabriel; Dhinakaran, V.; Usman, Mian (Universitas Muhammadiyah Yogyakarta, 2020)
Vitiligo is a skin disorder caused by a lack of melanin pigment in the skin, which causes white patches on certain parts of the skin because this melanin pigment is not able to produce the skin color. Previously, one of the treatments for vitiligo was using a UVB lamp with a 311 nm wavelength that could not yet be adjusted to dim the lights as safety when conducting therapy. Therefore, the research aims to design a simulation of the vitiligo therapy device equipped with a timer LED lamp, a safety of lighting, and the data storage. The data are stored in the SD Card to make it easier for patients to control changes before and after therapy. The simulation of this therapeutic apparatus is controlled using the Arduino Uno system and regulates lightning protection using a PWM circuit and ultrasonic sensors. The highest error obtained is 2.4%. at 5 cm. The overall device system, namely timer, buzzer, hour meter, and data storage has been working well and the error value is still within tolerance which is below 5%. Thus, it is hoped that this vitiligo therapy simulation device is able to operate as a real therapeutic device